Jovem Maia: cotidiano e condições sociais em Ixcán, Guatemala - Nones, Adriana Ines (2014)
In this writing I report the daily life and the socio-historic conditions of the Mayan youth in the municipality of Ixcan, Guatemala. I experienced the young diversity through the exchange of aspirations, challenges and personal pursuits. I witnessed, through the subtlety of the social relations, the tension, the care, and the relations between the different generations. This exercise demanded time as the interpersonal relationships require the perception of the bonds of belonging, the interweaving of the cultural relations and the creativity to survive during the times of historic and social changes. The historic conditions generated movements of disorder/reorder in the life of the Mayan people and resounds on the different experiences of the youth. The history of the youth interweaves with the history of their forbearers. The process of Spanish colonization, imposed other ways of life to the Mayan people, and the dream of the land, that was usurped during the thirty six years of the civil war, made of Ixcan, a place that represented the hope, an experience of horror and traumas. The violence of the conflicts destabilized and dissipated the social fabric, shaking familial, social, and communal relationships. Its images and noises impregnated the mind of the youth. The participation and the youth protagonism, after the Peace Deal in 1996, were of surmountable importance in the reestablishment of the peace that was extremely sought after. Today the media delineates new interconnections in the different youth outlooks